Rescue of Mutant CFTR Channel Activity by Investigational Co-Potentiator Therapy - Mafalda Bacalhau; Filipa C. Ferreira; Marcelo Folhadella M. F. Azevedo; Talita P. Rosa; Camilla D. Buarque; Miquéias Lopes-Pacheco (Biomedicines)
Background: The potentiator VX-770 (ivacaftor) has been approved as a monotherapy for over 95 cystic fibrosis (CF)-causing variants associated with gating/conductance defects of the CF transmembrane conductance regulator (CFTR) channel. However, despite its therapeutic success, VX-770 only partially restores CFTR activity for many of these variants, indicating they may benefit from the combination of potentiators exhibiting distinct mechanisms of action (i.e., co-potentiators). We previously identified LSO-24, a hydroxy-1,2,3-triazole-based compound, as a modest potentiator of p.Arg334Trp-CFTR, a variant with a conductance defect for which no modulator therapy is currently approved. Objective/Methods: We synthesized a new set of LSO-24 structure-based compounds, screened their effects on p.Arg334Trp-CFTR activity, and assessed the additivity of hit compounds to VX-770, ABBV-974, ABBV-3067, and apigenin. After validation by electrophysiological assays, the most promising hits were also assessed in cells expressing other variants with defective gating/conductance, namely p.Pro205Ser, p.Ser549Arg, p.Gly551Asp, p.Ser945Leu, and p.Gly1349Asp. Results: We found that five compounds were able to increase p.Arg334Trp-CFTR activity with similar efficacy, but slightly greater potency promoted by LSO-150 and LSO-153 (EC50: 1.01 and 1.26 μM, respectively). These two compounds also displayed a higher rescue of p.Arg334Trp-CFTR activity in combination with VX-770, ABBV-974, and ABBV-3067, but not with apigenin. When tested in cells expressing other CFTR variants, LSO-24 and its derivative LSO-150 increased CFTR activity for the variants p.Ser549Arg, p.Gly551Asp, and p.Ser945Leu with a further effect in combination with VX-770 or ABBV-3067. No potentiator was able to rescue CFTR activity in p.Pro205Ser-expressing cells, while p.Gly1349Asp-CFTR responded to VX-770 and ABBV-3067 but not to LSO-24 or LSO-150. Conclusions: Our data suggest that these new potentiators might share a common mechanism with apigenin, which is conceivably distinct from that of VX-770 and ABBV-3067. The additive rescue of p.Arg334Trp-, p.Ser549Arg-, p.Gly551Asp-, and p.Ser945Leu-CFTR also indicates that these variants could benefit from the development of a co-potentiator therapy.